Morphological changes in the brain in liver cirrhosis of alcoholic and viral etiology - A. M. Maybogin; M. K. Nedzvedz; N. V. Kornev (Acta Biomedica Scientifica)
Background. Hepatic encephalopathy is an actual problem of modern medicine. However, its pathogenesis and histological picture are currently insufficiently studied. Less is known about the impact of the nature of primary liver disease on pathogenesis and histological picture of hepatic encephalopathy. This determines the relevance of further morphological studies of the brain in the late stages of liver cirrhosis of various etiologies.The aim. To establish and compare the morphological changes in the brain in alcoholic liver cirrhosis and viral (hepatitis C virus (HCV)) cirrhosis.Materials and methods. The morphological study of the brain of 40 deceased in outcome of HCV-associated cirrhosis and 23 patients died in outcome of chronic alcoholism was carried out. Histological changes in various parts of the brain were studied using survey and elective stains. The immunohistochemical study of HCV NS3 and CD68 expression in different brain regions was performed in cases of HCV-infection.Results. The changes of neurons, glial cells and cerebral microvessels underlie in the basis of morphological picture of brain damage in both studied groups underlie that corresponds to the “classical” model of hepatic encephalopathy pathogenesis. At the same time, a number of morphological features were observed. The most prominent differences concerned the manifestations of the glial reaction. The productive changes of macroglial cells with the appearance of multiple Alzheimer’s astrocytes type 2 as well as spongious changes in subcortical white matter dominated in the observations of alcoholic cirrhosis. In contrast, microglia cells reaction (microgliosis) in white matter was noticed in HCV-associated cirrhosis.Conclusions. The differences in histological signs of brain in the terminal stages of liver disease of viral and alcoholic etiology are shown. They broaden current idea of morphological picture of hepatic encephalopathy, and may be used to study its pathogenesis.